Zia - O'Dell, Scott, 1898-1989. (New York : Bantam Doubleday Dell Books for Young Readers, 1995)
A young Indian girl, Zia, caught between the traditional world of her mother and the present world of the Mission, is helped by her aunt Karana whose story was told in "Island of the Blue Dolphins."
"A Yearling book."
Sequel to: Island of the Blue Dolphins.
5.2
5-8
Keywords: Indians of North America -- Fiction; Native Americans -- North America -- Fiction